2002
DOI: 10.1891/0047-2220.33.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Rehabilitation Services Received after Successful Closure: A Comparison by Race

Abstract: The purpose of this study was to investigate whether successfully closed (Status 26) African Americans and White Americans differed in the type of vocational rehabilitation (VR) services received. Authors used the chi-square and phi coefficient to ascertain the association and significance between the independent and dependent variables, respectively. The results revealed the three services most commonly received by African Americans were maintenance, transportation, and adjustment training. The three services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Within the public vocational rehabilitation (VR) program, tracking variables such as employment rates and outcomes, hours worked, wages, time in service, race, gender, and other participant characteristics can provide staff with important data to inform decision-making; provide support for staff, as well as hold them accountable; and offer a path forward for making improvements. Previous research has identified service delivery and outcome differences based on consumer race, gender, and other demographic variables within VR (Rosenthal et al, 2005;Wilson et al, 2002). In this regard, dashboards can serve as key tools to help agencies identify gaps and discrepancies and bolster an agency's capability to plan and improve programs, and measure their impact (Groomes et al, 2012).…”
Section: Background and Purposementioning
confidence: 99%
“…Within the public vocational rehabilitation (VR) program, tracking variables such as employment rates and outcomes, hours worked, wages, time in service, race, gender, and other participant characteristics can provide staff with important data to inform decision-making; provide support for staff, as well as hold them accountable; and offer a path forward for making improvements. Previous research has identified service delivery and outcome differences based on consumer race, gender, and other demographic variables within VR (Rosenthal et al, 2005;Wilson et al, 2002). In this regard, dashboards can serve as key tools to help agencies identify gaps and discrepancies and bolster an agency's capability to plan and improve programs, and measure their impact (Groomes et al, 2012).…”
Section: Background and Purposementioning
confidence: 99%
“…The RSA-911 is a major data source for evaluating the effectiveness of the VR system, particularly its services and the factors associated with receipt of VR services. The racial differentials in the VR acceptance rate, service provision, and successful rehabilitation rate (the rate of closures with continuous employment) have been always a concern of the rehabilitation field, and the RSA-911 has been intensively used to identify the level, causes, and consequences of these differentials (Cardoso, Romero, Chan, Dutta, & Rahimi, 2007;Cavenaugh, Giesen, & Steinman, 2006;Mwachofi, 2008;Mwachofi, Broyles, & Khaliq, 2009;Nazarov, 2013;Wilson, Harley, & Alston, 2001;Wilson & Senices, 2005;Wilson, Turner, & Jackson, 2002). The differences in earnings within the same occupational group between successfully rehabilitated individuals exiting the VR system and the sample of typical workers drawn from the national survey has been recently studied by Martin et al (2012).…”
Section: Rehabilitation Services Administration-911 Datamentioning
confidence: 99%
“…The VR program is not free from bias and can influence service provision and outcomes for PWDs. Studies have reported racialized differences in VR acceptance rates (Rosenthal et al, 2005) and service provision (Wilson et al, 2002). Specifically, White VR consumers were 80% to 91% more likely to be closed in self-employment, whereas female VR consumers were 26% to 30% less likely to be closed in self-employment (Yamamoto & Alverson, 2013, 2017).…”
mentioning
confidence: 99%